Race, Ethnicity and Football : Persisting Debates and Emergent Issues. - Burdsey, Daniel (Taylor & Francis, 2011)
Elucidating the linkages between race, ethnicity, gender and masculinity in football, this volume addresses topics such as the experience of Muslim players, recruitment of African players, devolution and national identities, minority ethnic clubs, "mixed-race" players, sectarianism, and foreign club ownership.